Phát triển năng lực mô hình hóa toán học cho sinh viên ngành kinh tế trong dạy học nội dung “Hệ phương trình tuyến tính” (học phần Đại số tuyến tính) - Nguyễn , Chiến Thắng; Thái , Thị Vân Anh (Tạp chí Giáo dục, 2023)
Mathematics is an important tool to solve practical problems, including those in the field of economics. In the training program for Economics students, teaching advanced Mathematics modules aims at helping learners improve their ability to use mathematical knowledge to solve practical problems in economics. The study proposes a mathematical modeling process in teaching Math modules for Economics students and illustrates this process in teaching content "Linear equation systems" in the Algebra module to develop mathematical modeling capacity for students. To develop mathematical modeling capacity for students through the mathematical modeling process in teaching Mathematics subjects effectively, lecturers need to invest time in researching documents, learning about practice and flexibly applying teaching methods for specific content.